Fate of Patients Unwilling or Unsuitable to Undergo Surgical Intervention for a Ruptured Abdominal Aortic Aneurysm. Issue 2 (February 2015) - van Beek, S.C.; Vahl, A.C.; Wisselink, W.; Balm, R.
Abstract : Introduction: The primary objective of this study was to assess the duration of in-hospital survival in 57 patients with ruptured abdominal aortic aneurysms (RAAA) who did not undergo surgical intervention. Report: Two hours after registration in the emergency room, 58% (95% CI 45–71) of patients were still alive. The median survival was 2.2 hours (interquartile range 1–18). In a subgroup including 26 haemodynamically stable patients, survival after 2 hours was 96% (95% CI 89–100). Conclusion: In patients with an RAAA without surgical intervention, the duration of in-hospital survival is limited. However, a group of haemodynamically stable patients can be identified in whom survival is much longer.